Impact of maloclusion on quality of life in adolescent: a literature review: Dampak maloklusi terhadap kualitas hidup anak usia remaja: sebuah kajian literatur - Donald R. Nahusona; Rika Damayanti Syarif; Nurfadillah Panggalo (Makassar Dental Journal PDGI Makassar, 2022)
National Basic Health Research of the Ministry of Health Republic of Indonesia in 2018 stated that 57.6% of the Indonesian population suffered from dental and oral health problems and only 10.2% of the population receives care and treatment from dental health personnel. One of the dental and oral health problems that are often encountered in the community is malocclu-sion. Malocclusion has a great impact on both individuals and society in terms of quality of life, anxiety, functional limits, and emotional conditions. Adolescence is an important stage in human life where appearance is an important and influential factor in social interaction. It is concluded that malocclusion has an impact on the quality of life in adolescent. The decrease in quality of life was more pronounced starting in malocclusion with severe criteria until more severe criteria Key words: adolescents, malocclusion, occlusion, oral health, quality of life